Teaching basic computer programming to young adults with intellectual disability - Stimoli, Maria Agatina; Di Blasi, Francesco Domenico; Maccarrone, Silvestro; Costanzo, Angela Antonia; Occhipinti, Paola; Buono, Serafino (Frontiers in education (Lausanne), 2024)
IntroductionTeaching computer programming can be challenging, especially for individuals with intellectual disability (ID) who exhibit a wide range of learning abilities and behavioral characteristics. This study aimed to investigate the effectiveness of an intervention designed to teach computer programming skills to individuals with ID.MethodFour women with ID, aged 27 to 54 years, were selected to participate in the study. Participants were taught computer programming using authoring software to create multimedia educational activities. A discrete trial teaching (DTT) approach was employed to teach specific skills and to gradually fade prompts to promote independent learning. A multiple-probe design across subjects was used to evaluate the effectiveness of the intervention. This design involved a baseline phase, a training phase with a most-to-least prompting procedure, and a 1-month follow-up phase to assess skill maintenance.ResultsThe results demonstrated that all participants were able to acquire the necessary programming skills and complete the assigned tasks independently.ConclusionComputer programming can provide valuable learning and development opportunities for individuals with ID. However, it is essential to tailor the instruction to individual needs and provide appropriate support.